Sustainable development and subnational governments : policy making and multi-level interactions - Bruyninckx, Hans, 1964-; Happaerts, Sander, 1983-; Brande, Karoline van den, 1983- (Palgrave Macmillan, 2012)
This book highlights the activities of a category of actors understudied in the field of governance for sustainable development. Situated between the local and the national level of governance, subnational governments have significant responsibilities in key issues for sustainable development. Firstly, the book studies how these governments have taken up the challenge of designing sustainable development policies domestically. Secondly, it examines subnational involvement in international decision-making on sustainable development, with particular attention to the interactions that take place between multiple levels of governance. With new empirical material on the experiences of subnational governments in seven countries across Western Europe and North America, the contributors consider what challenges they are facing on the eve of Rio+20.